Pengembangan Media HAM (Haji dan Umrah) berbasis iSpring Suite pada Mata Pelajaran Fiqih Kelas X di MA Al-Bairuny Sambong Dukuh Jombang - Fuadah, Fadlilah Faizatul; Rohmah, Hidayatur (YASIN, 2025)
Fiqih instruction in Class X at MA Al-Bairuny Sambong Dukuh Jombang remains predominantly lecture-based and relies solely on textbooks, resulting in student disengagement and low participation. This study aims to develop HAM (Hajj and Umrah) instructional media using iSpring Suite and to assess students’ responses to the media. The research employed a Research and Development (RnD) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection instruments included validation questionnaires for media experts, subject matter experts, and student response surveys. Media expert validation scores averaged 77% in the first round (categorized as valid) and 84% in the second round (categorized as highly valid). Subject matter expert validation scores were 90% and 93%, both falling within the highly valid category. Meanwhile, student response results yielded a score of 91%, indicating high practicality. These findings demonstrate that the HAM media developed with iSpring Suite is both feasible and practical for use in Fiqih learning. The study underscores the importance of innovative interactive digital media in fostering engaging and effective learning, particularly for procedural content such as Hajj and Umrah rituals.